Analisis Model Transportasi Tidak Seimbang pada Perusahaan Lima Pilar Distrubusi dengan Metode NWC dan Stepping Stone - Pesta Gultom; Rebeka Oktavia Purba; Windi Felisah Manalu; Tiara Sopianta Samosir; Linca Narsi Patresya Tamba (JOURNAL SAINS STUDENT RESEARCH, 2025)
The Lima Pilar Distribution Company is a company engaged in the distribution of electronic goods. Distribution of goods is a very crucial element in running a company. To achieve maximum profit, companies need to manage the delivery of goods in an efficient and appropriate manner. If there are several points of supply and demand locations that have varying shipping costs, then this problem can be overcome by the transportation method. This study applies the North West Corner (NWC) method to find an initial solution and the Stepping Stone method to obtain the best solution in the distribution of goods at the Lima Pilar Distribution Company. The distribution problem in this company is included in the category of unbalanced transportation because the amount of supply is greater than the amount of demand. The results of the analysis show that the initial solution obtained from the NWC method still has shortcomings in terms of cost efficiency, but after being optimized with the Stepping Stone method, a lower and more efficient total distribution cost is obtained. Thus, the application of the right transportation method can increase shipping efficiency and reduce overall logistics costs.